2013
DOI: 10.3390/ijerph10041202
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change is Likely to Worsen the Public Health Threat of Diarrheal Disease in Botswana

Abstract: Diarrheal disease is an important health challenge, accounting for the majority of childhood deaths globally. Climate change is expected to increase the global burden of diarrheal disease but little is known regarding climate drivers, particularly in Africa. Using health data from Botswana spanning a 30-year period (1974–2003), we evaluated monthly reports of diarrheal disease among patients presenting to Botswana health facilities and compared this to climatic variables. Diarrheal case incidence presents with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 92 publications
(102 reference statements)
13
99
0
3
Order By: Relevance
“…Cases only showed potential increases in the wettest months of July and August in the far future projections for RCPs 6.5 (8.3 and 7.9%) and 8.0 (17 and 21%) respectively. This finding corroborates that of a related study of diarrheal diseases in Botswana by Alexander et al (2013) where diarrheal disease incidences was suggested to increase with hot conditions and decline likely in the wet season. There is little difference among projected cholera case rates among the three scenarios for 2020-2035, for example in May and June increases ranges from 13-16% and 10-16% respectively, but larger differences among the scenarios occur for 2060-2075 after the RCP emissions scenarios diverge (Moss et al, 2010), with May increases of about 20%, 27%, and 40% for RCP 2.6, 6.0, and 8.5 respectively.…”
Section: Cholera Projectionssupporting
confidence: 82%
See 2 more Smart Citations
“…Cases only showed potential increases in the wettest months of July and August in the far future projections for RCPs 6.5 (8.3 and 7.9%) and 8.0 (17 and 21%) respectively. This finding corroborates that of a related study of diarrheal diseases in Botswana by Alexander et al (2013) where diarrheal disease incidences was suggested to increase with hot conditions and decline likely in the wet season. There is little difference among projected cholera case rates among the three scenarios for 2020-2035, for example in May and June increases ranges from 13-16% and 10-16% respectively, but larger differences among the scenarios occur for 2060-2075 after the RCP emissions scenarios diverge (Moss et al, 2010), with May increases of about 20%, 27%, and 40% for RCP 2.6, 6.0, and 8.5 respectively.…”
Section: Cholera Projectionssupporting
confidence: 82%
“…In order to assess uncertainties in the projections, multi model ensemble from ten monthly AOGCMs simulations from CMIP5 were used (e.g., Giorgi, 2005). Given that projected climate changes in northern Nigeria are similar for other regions of the Sahel (Chou et al, 2013), as are the climate-driven dynamics of cholera transmission (e.g., Alexander et al, 2013), these results may be broadly applicable throughout Sahelian Africa. It is noteworthy that the WAM which brings about precipitation in the Sahel is not well simulated in climate models (Bock et al, 2011;Marsham et al, 2013); however, the AOGCMs have vigorously improved if compared with the previous GCMs; they now include the representation of the ocean, atmospheric chemistry, vegetation, carbon cycle, land surface, aerosols, and sea ice at a finer spatial resolution (McMichael et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some physical indicators in the 1st quadrant of the PCA interacted with epidemiological indicators, the combination of which led to moderate responses to climate change impacts and also confirming that clusters of indicators were most likely to have direct impacts on public health. The study affirmed the emerging relevance which is attached to climate change and diarrheal diseases (Alexander et al, 2013;Carlton et al, 2014) by eliciting highest indicators in all three districts as compared to malaria and CSM, the latter only studied in a single district.…”
Section: Baseline Characteristics Of Health Sector Indicators and CLIsupporting
confidence: 58%
“…For example, in Switzerland, higher water vapor pressure and temperature were associated with increased risks for developing communityacquired Legionnaires' disease 6 . In Botswana, the elevation of annual minimum temperature was considered as a critical factor for the continual ascent in the number of diarrheal diseases reported during the period of 1974-2003 7 . The result of current study revealed that temperature was positively correlated with BD incidences in Guangzhou, with each 1°C rise in temperature corresponding to an increase of 3.60% in the monthly number of confi rmed BD cases.…”
mentioning
confidence: 99%